Construction and psychometric properties of a questionnaire to measure the level of addiction to online video games (CUAVIR) in the city of Juliaca – 2020 - Bellido Mamani, Yeni (2020)
Objective: To construct and determine the psychometric properties of a questionnaire to measure thelevel of addiction to online video games, in adolescents and young people whose ages range from 12to 25 years. Methodology: Non-experimental design, type psychometric study, with a cross sectionand quantitative approach. The sample is made up of 145 subjects who voluntarily participated in thestudy from an outpatient application, the instrument constructed called “CUAVIR”, consists of 42 itemsdistributed in 5 dimensions (Abstinence, Resistance, Interference with Activities, Dependence andAwareness of Illness). For content validity, the criterion of expert judges was applied, the results wereanalyzed through the Binomial Test, the validity coefficient was measured through Aiken’s V, and the  alphacoefficient was used to measure the degree of internal consistency of Cronbach. Results: The Binominal test determined that the dimensions and items are adequate and significant, with respect to contentvalidity, Aiken’s V yielded confidence intervals of 0.89 for the items, which indicates that the questionnaire has a high degree validity in four essential criteria (Congruence, Clarity, Domain of the Construct and Context). Regarding internal consistency, Cronbach’s alpha coefficient showed that dissensions obtainedvalues of 0.942, which shows that the instrument is reliable. The confirmatory factor analysis showed that the instrument has characteristics that allow processing by the (CFA) and the total variance explained showed that with five factors the total accumulated variance can be explained by 52.358%, which would indicate that the work with five dimensions is appropriate. Conclusion: the questionnaire to measure the level of addiction to online video games (CUAVIR) shows good internal consistency and construct validity.